Athena’s Image in Fine Art and Literature of Art Nouveau - Bartosh, Natalia Yu. (Actual Problems of Theory and History of Art, 2015)
The image of the goddess Athena in fine art and literature of Art Nouveau is analysed through the lenses of the archetypal plot of sacred marriage. The evolution of the image development in Art Nouveau is considered within the framework of interrelation between literature and fine art. Monumental figure of Athena does not fit the style canons of the epoch, differing drastically from feminine images of Art Nouveau. In the Art Nouveau literature — from the goddess in O. Wilde’s poem “Charmides” to Sophia in the works by Vladimir Soloviov, and the mysterious Lady-love of the Russian symbolists’ poems (A. Blok, V. Ivanov) — Athena appears to be presented quite different from her ancient prototype. “Charmides”, which is often falsely referred to as erotic poetry, demonstrates the specific treatment of the sacred marriage theme by the Art Nouveau literary tradition and the importance of Athena’s role assigned by this tradition. The origins of the Art Nouveau vision in painting are revealed in “Perseus Cycle” by Edward Burne-Jones, and the climax of its development is evident in posters, pictures and mascarons created by the artists of German and Austrian Secession — F. Stuck, G. Klimt, and K. Moser. Important are erotic versions of the goddess’s image presented in mass culture of fin de siècle (picture-cards by Louis Théophile Hingre et al.), as well as the comparison of Athena’s and Gorgo’s images. In Burne-Jones’s creations they are depicted as correlatives, whereas presentation of Gorgo and chtonic attributes (the owl and the snake) in the art of Secession displaces Athena from her hypostasis of the goddess of reason. The analysis of the archetypal images in the Art Nouveau literature and fine art shows the strict logical conditionality of Athena’s image development, which seems paradoxical at first glance: despite the stable mythological concept of Athena’s virilism and asexuality, she is given the power of bestowing creativity through symbolic connection with a creator.